Contaminant hydrogeology - Fetter, C. W. (Estados Unidos | ESTADOS UNIDOS Prentice-Hall / Waveland -EE-UU, 1999)
Contents: Introduction; Mass transport in saturated media; Transformation, retardation and attenuation of solutes; Flow and mass transport in the vadose zone; Multiphase flow; Inorganic chemicals in ground water; Organic compounds in ground water; Ground water and soil monitoring; Site remediation
Sin Especificar
Keywords: Hidrogeología | Aguas subterráneas-Contaminación